Association of labor induction or stimulation with infant mortality in women with failed versus successful trial of labor after prior cesarean*. (19th March 2013) - Chen, Han-Yang; Chauhan, Suneet P.; Grobman, William A.; Ananth, Cande V.; Vintzileos, Anthony M.; Abuhamad, Alfred Z.
Abstract: Objective : To compare infant mortality rates among women with a failed versus successful trial of labor after cesarean (TOLAC) following labor induction or stimulation. Study design : Using US linked birth and infant death cohort data (2000–2004), we identified women who delivered non-anomalous singleton births at 34–41 weeks with TOLAC whose labors were induced or stimulated. Multivariable log-binomial regression models were fitted to estimate the association between TOLAC success and infant mortality. Results : Of the 164, 113 women who underwent TOLAC, 41% were unsuccessful. After adjustment for potential confounding factors, a failed TOLAC was associated with a 1.4 fold (95% confidence interval [CI] 1.1, 1.7) increased risk of infant mortality. Conclusions : Among women undergoing labor induction or stimulation, a failed TOLAC is associated with higher likelihood of infant mortality.